2021
DOI: 10.1016/j.jpeds.2021.01.027
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of the Panbio Severe Acute Respiratory Syndrome Coronavirus 2 Antigen Rapid Test Compared with Reverse-Transcriptase Polymerase Chain Reaction Testing of Nasopharyngeal Samples in the Pediatric Population

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
6
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 12 publications
4
50
6
4
Order By: Relevance
“…Specificity for all used RDT was above 99·6%, which is comparable to manufacturers’ data (99·4% (Panbio™), 99·8% (MEDsan®), or >99·9% (NADAL®)). Sensitivity and specificity data is comparable with performance data from other studies: The Panbio™ RDT has been evaluated in several studies, [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] and reported sensitivity values range from 44·6% [12] to 91·7% [13] . The specificity was continuously in the range of 98·9% [13] to 100%.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Specificity for all used RDT was above 99·6%, which is comparable to manufacturers’ data (99·4% (Panbio™), 99·8% (MEDsan®), or >99·9% (NADAL®)). Sensitivity and specificity data is comparable with performance data from other studies: The Panbio™ RDT has been evaluated in several studies, [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] and reported sensitivity values range from 44·6% [12] to 91·7% [13] . The specificity was continuously in the range of 98·9% [13] to 100%.…”
Section: Discussionsupporting
confidence: 80%
“…The SARS-CoV-2 prevalence in the study population of 2 % was higher compared to the general population but lower compared to studies mainly conducted in symptomatic patients [ [14] , [15] , [16] , [17] , 21 ]. PPV was significantly higher in symptomatic persons compared to asymptomatic which reflects mainly a presumably higher prevalence but also a higher sensitivity of the tests due to higher viral loads.…”
Section: Discussioncontrasting
confidence: 59%
“…Our results showed an accurate performance of Ag-RDTs in the age-group 5–14, unlike other studies [ 19 , 20 ]. The differences between age-groups could be related to differences in SARS-CoV-2 viral load [ 20 , 21 ]. However, age-related differences in the performance of Ag-RDT remain unknown.…”
Section: Discussioncontrasting
confidence: 90%
“…Of the 13 TGA approved antigen tests, the Panbio COVID-19 Ag rapid test (Abbott) currently has the most peer-reviewed literature, including for children. 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 Two early studies of the Panbio COVID-19 Ag rapid test found sensitivity between 73–81% and 100% specificity. 61 , 62 In addition, FINDdx independent evaluations found Panbio sensitivity for NPS in symptomatic persons to be 85.5% (95%CI 78.2–90.6%) with clinical specificity of 100% (95%CI 99.1–100%).…”
Section: Antigen Testsmentioning
confidence: 99%